Impacts of CR1 genetic variants on cerebrospinal fluid and neuroimaging biomarkers in alzheimer's disease - Xi-chen Zhu; Wen-zhuo Dai; Tao Ma (BMC, 2020)
Abstract Background The complement component (3b/4b) receptor 1 gene (CR1) gene has been proved to affect the susceptibility of Alzheimer's disease (AD) in different ethnic and districts groups. However, the effect of CR1 genetic variants on amyloid β (Aβ) metabolism of AD human is still unclear. Hence, the aim of this study was to investigate genetic influences of CR1 gene on Aβ metabolism. Methods All data of AD patients and normal controls (NC) were obtained from alzheimer's disease neuroimaging initiative database (ADNI) database. In order to assess the effect of each single nucleotide polymorphism (SNP) of CR1 on Aβ metabolism, the PLINK software was used to conduct the quality control procedures to enroll appropriate SNPs. Moreover, the correlation between CR1 genotypes and Aβ metabolism in all participants were estimated with multiple linear regression models. Results After quality control procedures, a total of 329 samples and 83 SNPs were enrolled in our study. Moreover, our results identified five SNPs (rs10494884, rs11118322, rs1323721, rs17259045 and rs41308433), which were linked to Aβ accumulation in brain. In further analyses, rs17259045 was found to decrease Aβ accumulation among AD patients. Additionally, our study revealed the genetic variants in rs12567945 could increase CSF Aβ42 in NC population. Conclusions Our study had revealed several novel SNPs in CR1 genes which might be involved in the progression of AD via regulating Aβ accumulation. These findings will provide a new basis for the diagnosis and treatment AD.